Why Social Constructionists Should Embrace Minimalist Race. (20th July 2022) - Hardimon, Michael
ABSTRACT: My thesis is that social constructionists should embrace minimalist race. By this I mean they should accept the minimalist concept of race and the existence of minimalist races. They are likely to reject this suggestion because they are antirealists about biological race. But their antirealism about biological race is based on their identification of the biological concept of race with the racialist concept of race. The minimalist concept of race is free of the invidious features that make the racialist concept objectionable. It represents race as ancestry marked by patterns of visible physical differences. The reasons social constructionists have to reject the racialist concept of race do not extend to the minimalist concept of race. Social constructionists should accept that minimalist races exist, because it is overwhelmingly plausible that such races exist. Furthermore, they need minimalist races to account for the biological correlate of social race and to secure the biological materials the project of social construction requires.